Intraoperative ice pack application for uvulopalatoplasty pain reduction: A randomized controlled trial12. (20th August 2012) - Rotenberg, Brian W.; Wickens, Brandon; Parnes, Jason
Abstract Objectives/Hypothesis: Pain after uvulopalatoplasty continues to cause patients significant morbidity, especially from the tonsillectomy portion. The literature describes multiple techniques to reduce post‐tonsillectomy pain, none being definitive. The purpose of this study was to evaluate the effect of intraoperative ice pack application on post‐uvulopalatoplasty pain. Study Design: Single‐blinded, randomized controlled trial. Methods: After inclusion and exclusion criteria were met, patients were enrolled and randomized, and subsequently underwent standard electrocautery uvulopalatoplasty. Packs were placed into the tonsillar fossae immediately following tonsil removal and into the palate after the palatoplasty. Patients then completed a questionnaire that evaluated their experience for 10 days following surgery. The primary outcome was pain rated on a visual analog scale. Return to work and return to normal diet were also assessed. T test and Mann‐Whitney statistical analyses, as well as routine descriptive statistics, were conducted. Results: Eighteen subjects were recruited. Patients that received intraoperative cold packs experienced a statistically significant change in VAS average pain [3.4 ± 1.1 cm (p = 0.00001)] when compared with patients receiving room temperature packs. No difference in return to work (p = 0.16) and return to normal diet (p = 0.12) was identified. Conclusions: Intraoperative ice pack administration results in significantly reduced pain following electrocautery uvulopalatoplasty.